Direct cigarette smoke exposure to 3D epithelial cell cultures by an aerosol exposure system - Development and evaluation of an in vitro model for COPD with direct cigarette smoke exposure on small airway epithelial cells in the air-liquid interface by the Vitrocell smoking system - Knudsen, Veronika (My University, 2021)
Chronic Obstructive Pulmonary Disease (COPD) is a chronic inflammatory and progressive lung disease that causes obstructed airflow from the lungs. The Global Burden of Disease Study reports a prevalence of 251 million cases of COPD globally in 2016 and classify the disease as the third most common causes of deaths worldwide. Cigarette smoke exposure is one of the major risk factors for developing COPD. Up to 40% of smokers develop COPD over time, and continuous smoking drives the development and progression of the disease. The aim of this project was to develop and evaluate an in vitro model for direct whole cigarette smoke exposure on small airway epithelial cells (SAECs) with an automated aerosol system (Vitrocell smoking system). SAECs from three COPD donors and two healthy donor, cultured in the air-liquid interface (ALI), were used. To examine the effects of cigarette smoke on airway epithelium, cells were exposed to either one or three non-toxic doses of smoke, and samples were collected 24 and 48 hours post exposure. Cytotoxicity, barrier integrity, ciliary beat frequency, gene expression and cytokine expression were investigated. Cigarette smoke effectively increased the amount of inflammatory mediators IL-6 and IL-8 in supernatants from smoke-exposed samples, and up-regulated inflammatory gene expression of IL-8, and gene expression of antioxidants SRXN1 and HMOX1. This project was performed at AstraZeneca in the Bioscience COPD IPF Department within the Early Respiratory and Immunology R&D unit located in Gothenburg, Sweden.
Keywords: COPD, Small airway epithelial cells, cigarette smoke, Vitrocell system, RT-PCR, air liquid interface, ciliary beat frequency